Dampak Konsumsi E-Cigarettes di Negara Tujuan Terhadap Volume Ekspor Tembakau Indonesia - Ayuningsih, Ni Nyoman Adhisri; Kartika Yudha, I Made Endra (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The tobacco commodity is a leading commodity because it is able to make a significant contribution to the country's economy. However, there has been a decrease in the volume of Indonesian tobacco exports followed by a decrease in global cigarette consumption, which is indicated because there are substitute goods, namely e-cigarettes. This study aims to determine the factors that can affect the volume of Indonesian tobacco exports in nine of Indonesia's tobacco trading partner countries during the period 2003-2022. The variables analyzed include the amount of production, exchange rate, foreign investment, economic growth, and dummy of e-cigarette legalization policy. The analysis technique used was panel data regression analysis. The results showed that all variables simultaneously influenced the volume of Indonesian tobacco exports to nine trading partner countries. Partially, the exchange rate variable, foreign investment has a positive and significant effect on the volume of Indonesian tobacco exports. In addition, the legalization policy variable produces a probability that the volume of Indonesian tobacco exports to trading partner countries that legalize e-cigarettes will be higher than if Indonesia exports to countries that prohibit e-cigarettes. Meanwhile, the variables of total production and economic growth do not have a significant influence on the volume of Indonesian tobacco exports to nine trading partner countries during the period 2003-2022.